ПРО СТАНІСЛАВІВ І СТАНІСЛАВЦІВ - Баран, Є. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Tadeusz Olszański. Stanislawów jednak żyje. – Warszawa: Wydawnictwo Iskry, 2010. – 152 s.